Meningkatkan Hasil Belajar Siswa Pada Materi Aku citra Allah Yang Unik dengan Model Problem Based Learning di Kelas VII SMP Negeri 4 Lahewa - Veronika Suasani Nazara (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The independent curriculum emphasizes the Pancasila student profile. In this classroom action research, the researcher focuses on the dimension of independence which is based on the importance of forming strong character and mental attitudes in the younger generation, especially in facing complex global challenges. Improving learning outcomes through the PBL model on the material I Am the Unique Image of God. Promises. The Class Action Research Report in this study aims to find out whether student learning achievement has increased after implementing the Problem Based Learning Model in Catholic Religious Education and Character Education Subjects for Students in Class VII of SMPN 4 Lahewa in 2023/2024? The research object is the Problem Based Learning (PBL) Model, the form of research is Classroom Action Research with a cycle model, each cycle consists of four stages including: planning stage, implementation stage, observation stage and reflection stage. The data analysis technique used consists of data reduction by selecting raw data into information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results that refer to the problem formulation. The use of the Problem Based Learning model according to the syntax which includes orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, is effective in helping increase learning motivation and student independence in material I Am the Unique Image of God in class VIII of SMPN 4 Lahewa The data collection technique used by researchers was to observe students' activities guided by the P3 rubric. The results of observations from the three participants from the five students in cycle 1 averaged 74% and in cycle II 88% while the learning outcomes were in cycle! I the average was 81.5%, and in cycle II it increased to an average of 86.2%. The increase was seen to be 14% higher than before.